Analysis Study of Parental Choice of Education in The Millenial Era - Fauzi, Ahmad; BR, Rosyadi; Baharun, Hasan (Nadwa: Jurnal Pendidikan Islam, 2018)
This article discusses parents' choices about the model of Islamic education in the millennial era. This study uses the library method. The results showed that parents had several criteria in determining the choice of educational models in the millennial era, namely a). schools that provide a lot of religious material b). combining religion and science, c). giving reinforcement to monotheism, d). madrasas that have vision, mission with good management. E). madrasas that have the same status as public schools.Â AbstrakArtikel ini membahas pilihan orang tua tentang model pendidikan Islam di era milenial. Penelitian ini menggunakan metode kepustakaan. Hasil penelitian menunjukkan bahwa orangtua memiliki beberapa kriteria dalam menentukan pilihan model pendidikan di era millennial yaitu a). sekolah yang banyak memberikan materi agama b). mengkombinasikan agama dan sains, c). memberikan penguatan pada tauhid, d). madrasah yang memiliki visi, misi dengan pengelolaan manajemen yang baik. E). madrasah yang memiliki status yang sama dengan sekolah umum Â